Independent relationships between different domains of physical activity and depressive symptoms among 60,202 Brazilian adults - Werneck, André O. [UNESP] (2020)
Objective: To analyze the association between four key different physical activity (PA) domains and depressive symptoms among Brazilian adults. Methods: Data from the Brazilian National Health Survey (n = 60,202; ≥18 years) were used. PA across four different domains (leisure, transport, occupational and household) was collected through specific questionnaires. The cutoff point adopted in each domain was 150 min/week. Depression was evaluated through the Patient Health Questionnaire-9. Multivariable adjusted linear and logistic regression models were applied. Results: Leisure PA was associated with lower depressive symptoms [β: −0.008 (95% CI: −0.010 to −0.005); OR: 0.69 (95% CI: 0.59 to 0.81)]. Transport PA was also associated with lower depressive symptoms among older adults [β −0.008 (−0.012 to −0.003); OR: 0.70 (95% CI: 0.53–0.94)] but not middle-aged adults. On the other hand, occupational PA [β: 0.003 (95% CI: 0.002 to 0.005); OR: 1.62 (95% CI: 1.38 to 1.91)] and household PA [β: 0.009 (95% CI: 0.006 to 0.012); OR: 1.57 (95% CI: 1.37 to 1.79)] were associated with higher depressive symptoms. Conclusion: The association between PA and depression symptoms varies according to the domains of PA and some appear independent from each other. While leisure PA is associated with fewer depressive symptoms; occupational and household PA appear to be associated with an increased depression risk.